Oxygen - Shepard, Richard; Tierney, Maura, 1965-; Brody, Adrien; Naughton, James, 1945-; Robins, Laila; Calderon, Paul.; Krupa, Olek.; Baker, Dylan; Kinney, Terry; Curb Entertainment (Firm); Paddy Wagon Productions; Abandon Pictures (Firm); et al. (Encino, CA : Ardustry Home Entertainment, 2003)
Deep in the woods, in a makeshift coffin lies a woman whose only hope is mercy from the psychotic man who buried her or the power of a cop who can break him. There is no light, no time, no escape and the oxygen is running out.
Title from container.
Originally released as motion picture in 1998.
Special features: cast filmographies; video and theatrical trailers; audio commentary from Adrien Brody, Maura Tierney, and director Richard Shepard.
Executive producers, Eric Reichenbaum, Karen J. Lauder, Marcus Ticotin ; producers, Jonathan Stern, Richard Shepard, Carole Curb Nemoy, Mike Curb ; music, Rolfe Kent ; costume designer, Barbara Presar ; director of photography, Sarah Cawley.
Maura Tierney, Adrien Brody, James Naughton, Laila Robins, Paul Calderon, Olek Krupa, Dylan Baker, Terry Kinney.
Rated R.
Keywords: Attempted murder -- Drama; Psychopaths -- Drama; Feature films; Detective and mystery films; Spanish language materials